Master 5 utilities in 5 minutes. - Bohon, Cory.
Ever noticed that Utilities folder inside of your application folder and wondered what the stuff in it is for? Can those utilities control the weather...or may be give you superpowers? The reality is less exciting, but they're still incredibly useful to even the newest Mac user. In fact, the built-in Mac utilities are so useful that the folder has its own shortcut key combination. You can easily get to the Utilities folder in any Finder window by pressing Command+Shift+U. So open 'er up., and let's take a five-minute tour of what's inside.
Keywords: Macintosh (Computer); iMac; Snow Leopard; Console; Color Sync Utility; Disk utility; Network utility